Monitoring of soybean mechanical harvesting as a function of plot shapes - Paixão, Carla S.S. [UNESP]; Alcântara, Aline S. [UNESP]; Voltarelli, Murilo A.; da Silva, Rouverson P. [UNESP]; Tavares, Tiago de O. [UNESP] (FapUNIFESP (SciELO), 2017)
Information on harvester performance is important in the management and optimization of mechanized agricultural systems. In this sense, the aim of this study was to monitor the operation quality of soybean mechanical harvesting in different plot shapes by means of statistical process control. The harvest was carried out in an agricultural area of a farm located in Uberaba, MG, Brazil, with an experimental design based on the assumptions of statistical quality control and 18, 28, and 24 replications for irregular, rectangular, and trapezoidal plots, respectively. The variables and/or quality indicators of harvester performance were forward speed, engine speed, cylinder speed, and concave opening. The lowest variation occurred in the irregular plot for the quality indicators forward speed and engine speed of harvester. Engine speed and the concave opening of harvester were unstable for all plot shapes. Only the cylinder speed of the soybean harvester presented process stability during operation for the three plot shapes.
Keywords: Glycine max (L.) Merrill; Grain harvester; Harvester machine performance; Statistical quality control